Delay of Health Care Seeking Among TB patients in Kassala State Kassala Hospital -Sudan (2013) - Khalid, Fatima A.; Abdalla, Abdulraheem A.; El-bari, El-Basher Gesm (Gezira Journal of Health Sciences, 2018)
Background: Delay of health seeking care among tuberculous (TB) patients is a common problem that might contribute to the high burden of TB and increase the cost  of care for patients , families and public health system. Little is known about delays before the start of TB therapy in eastern Sudan. This study aimed to determine the factors associated with delay care seeking behavior in TB cases. Methods: A cross- sectional descriptive study was held at chest department, Kassala Teaching Hospital, during April to June 2013. TB patients were interviewed using pretested questionnaire that was filled by trained medical students to gather information about their knowledge of TB, and factors associated with delay of care seeking. Collected data were analyzed using SPSS for windows version 16.0. Results: Of 221 TB cases , 199 (90%) of them looked for treatment after setting of the most TB symptoms in period greater than three weeks. 155 (70.1%) looked for treatment guided by their relatives or friends, or due to un-response to self-medication. 150 (67.9%), and 164 (74.2%) came to hospital because they thought that their treatment should be at hospital. They mentioned different reasons associated with delay of seeking care as self-medication 119 (53.8), far distance to hospital 119 (53.8%), transport difficulties 113 (51.1%) and stigma 111 (50.2%).